The Evolution and Future of Virtual Reality in Geographic Information Systems - Arun Kumar Epuri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
MarketsandMarkets, "Geographic Information System (GIS) Market," 2020. [Online]. Available: https://www.marketsandmarkets.com/Market-Reports/geographic-information-system-market-55818039.html Grand View Research, "Augmented Reality & Virtual Reality Market Size, Share & Trends Analysis Report By Technology (Augmented Reality, Virtual Reality), By Component, By Device Type, By Application, By Region, And Segment Forecasts, 2021 - 2028," Feb. 2021. [Online]. Available: https://www.gmiresearch.com/report/augmented-reality-and-virtual-reality-market/ P. Cozzi and K. Ring, 3D Engine Design for Virtual Globes. CRC Press, 2011. [Online]. Available: https://virtualglobebook.com/3DEngineDesignForVirtualGlobesChapter1.pdf M. Dodge, M. McDerby, and M. Turner, Geographic Visualization: Concepts, Tools and Applications. John Wiley & Sons, 2023. [Online]. Available: https://onlinelibrary.wiley.com/doi/book/10.1002/9780470987643 L. Herman, T. Řezník, Z. Stachoň, and D. Russnák, "The Design and Testing of 3DmoveR: An Experimental Tool for Usability Studies of Interactive 3D Maps," Cartographic Perspectives, no. 90, pp. 31–63, 2018. [Online]. Available: https://doi.org/10.14714/CP90.1411 H. Wu, Z. He, and J. Gong, "A virtual globe-based 3D visualization and interactive framework for public participation in urban planning processes," Computers, Environment and Urban Systems, vol. 34, no. 4, pp. 291–298, 2010. [Online]. Available: https://doi.org/10.1016/j.compenvurbsys.2009.12.001 K. A. Ohori, F. Biljecki, A. Diakité, T. Krijnen, H. Ledoux, and J. Stoter, "Towards an integration of GIS and BIM data: What are the geometric and topological issues?," ISPRS Annals of Photogrammetry, Remote Sensing and Spatial Information Sciences, vol. IV-4/W6, pp. 1–8, 2018. [Online]. Available: https://doi.org/10.5194/isprs-annals-IV-4-W6-1-2018 P. Fraga-Lamas, T. M. Fernández-Caramés, Ó. Blanco-Novoa, and M. A. Vilar-Montesinos, "A Review on Industrial Augmented Reality Systems for the Industry 4.0 Shipyard," IEEE Access, vol. 6, pp. 13358-13375, 2018. [Online]. Available: https://doi.org/10.1109/ACCESS.2018.2808326 M. Haklay, A. Singleton, and C. Parker, "Web Mapping 2.0: The Neogeography of the GeoWeb," Geography Compass, vol. 2, no. 6, pp. 2011-2039, 2008. [Online]. Available: https://doi.org/10.1111/j.1749-8198.2008.00167.x H. Huang, M. Chen, and B. Guo, "Gamification and Serious Games for Personalized Health," Sensors, vol. 21, no. 5, p. 1671, Feb. 2021. [Online]. Available: https://ebooks.iospress.nl/publication/21449
Keywords: Virtual Reality; Augmented Reality; Geographic Information Systems; 3D Visualization; Spatial Data Analysis